An introductory overview on representation of dissident sexualities, abjection, and subversion in queer Gothic fiction - Andrio J. R. dos Santos (Moderna Språk)
Queer Gothic may be considered one of the most recent subgenres of Gothic literature, being understood as a type of fiction in which body, gender and sexuality assume a central role. I approach the representation of queer sexualities in queer Gothic works, basing my analysis on the theory of abjection, as well as on other authors who work with Gothic fiction and Queer Studies, such as Judith Butler (1990), William Hughes and Andrew L Smith (2009) and Paulina Palmer (2016). My analysis consists of drawing a critical panorama, then commenting on Gothic works such as The Monk (1796), by Matthew Gregory Lewis, and The Fall of the House of Usher (1839), by Edgar Allan Poe, culminating in contemporary works such as the novel The Lazarus Heart (1998), by the trans author Poppy Z. Brite. It is possible to consider that in the aforementioned works Queer desires are articulated with supernatural or psychological phantasmagorias, assuming a liminal aspect which denounces the fragmentation of the Queer subject in face of hegemonic society. On the other hand, the representation of Queer sexualities has subversive potentials, while the hegemonic discourse imposes on them the stigma of abjection.